Kinetics and mechanism of large rate enhancement in an Acidic Aqueous Cleavage of the Tertiary Amide Bond of N-(2-Methoxyphenyl)-N'-Morpholinophthalamide (1) - Ariffin, Azhar; Khan, M.N.; Sim, Y.L. (2008)
The rate of conversion of 1 to N-(2-methoxyphenyl)phthalimide (2) within [HCI] range 5.0 x 10(-3)-1.0 M at 1.0 M ionic strength (by NaCl) reveals the presence of both uncatalyzed and specific acid-catalyzed kinetic terms in the rate law. Intramolecular carboxamide group-assisted cleavage of amide bond of 1 reveals rate enhancement of much larger than 10(6)-fold compared to the expected rate of analogous intermolecular reaction. (C) 2008 Elsevier Inc. All rights reserved.